Dilating Vascular Diseases: Pathophysiology and Clinical Aspects - Ertan Yetkin; Selcuk Ozturk (International Journal of Vascular Medicine)
Atherosclerotic disease of the vessels is a significant problem affecting mortality and morbidity all over the world. However, dilatation of the vessels either in the arterial system or in the venous territory is another vessel disease. Varicocele, pelvic, and peripheral varicose veins and hemorrhoids are aneurysms of the venous vascular regions and have been defined as dilating venous disease, recently. Coronary artery ectasia, intracranial aneurysm, and abdominal aortic aneurysm are examples of arterial dilating vascular diseases. Mostly, they have been defined as variants of atherosclerosis. Although there are some similarities in terms of pathogenesis, they are distinct from atherosclerotic disease of the vessels. In addition, pathophysiological and histological similarities and clinical coexistence of these diseases have been demonstrated both in the arterial and in the venous system. This situation underlies the thought that dilatation of the vessels in any vascular territory should be considered as a systemic vessel wall disease rather than being a local disease of any vessel. These patients should be evaluated for other dilating vascular diseases in a systematic manner.